The beautiful and the sublime: Kantian aesthetics in Beethoven’s Symphony No. 6 - Cooper, Samuel, author; Waddell, Rachel, advisor; Kesikli, Egemen, committee member; Romagni, Domenica, committee member (Colorado State University. Libraries, 2026)
This thesis examines Beethoven's Symphony No. 6 in F major, Op. 68 through the aesthetic philosophy of Immanuel Kant, arguing that the work traces a progression from the Beautiful to the Sublime across its five movements. After outlining Kant's distinction between these categories and situating the symphony within the pastoral tradition and early nineteenth-century Viennese symphonic culture, the study offers close musical analysis of each movement. It demonstrates how Beethoven's use of form, irregular phrasing, and silence shapes a coherent experiential trajectory: the first three movements embody the stability and perceptual harmony of the Beautiful, while the final two movements confront and ultimately reconcile the destabilizing force of the Sublime. By integrating philosophical aesthetics with analytical and interpretive perspectives, this study reframes the Pastoral Symphony not simply as program music, but as a work that constructs a large-scale aesthetic experience, offering new insights for both scholarship and performance.
Keywords: conducting; music theory; Pastoral; Kant; Beethoven; musicology